2009
DOI: 10.1542/peds.2008-1578c
|View full text |Cite
|
Sign up to set email alerts
|

Linking Process to Outcome: Are We Training Pediatricians to Meet Evolving Health Care Needs?

Abstract: The Residency Review and Redesign in Pediatrics (R 3 P) Project began in 2005 and will have been completed in 2009. The purpose was to conduct a comprehensive reassessment of general pediatric residency education. The project convened 3 major colloquia supplemented by numerous meetings of an R 3 P committee and by surveys of residents, subspecialty fellows, and generalist and subspecialty practitioners. A principal conclusion was that resident learning opportunities should be more flexibly directed toward the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…We recognize that the competencies required of paediatricians are constantly evolving and may be different for different types of paediatricians. This observation is in keeping with the Residency Review and Redesign project (R 3 P) participants conclusions in the US that residency training should be tailored to meet the diverse career needs of individuals who choose to care for disparate patients, in diverse settings, with a variety of health-related needs ( Jones et al 2009;Leslie 2009). Residency training programmes should allow flexibility and take a patient-based and familycentred perspective, tailoring training to the diverse and emerging health care needs of the paediatric population ( Jones et al 2009;Leslie 2009).…”
Section: Training Needssupporting
confidence: 66%
See 1 more Smart Citation
“…We recognize that the competencies required of paediatricians are constantly evolving and may be different for different types of paediatricians. This observation is in keeping with the Residency Review and Redesign project (R 3 P) participants conclusions in the US that residency training should be tailored to meet the diverse career needs of individuals who choose to care for disparate patients, in diverse settings, with a variety of health-related needs ( Jones et al 2009;Leslie 2009). Residency training programmes should allow flexibility and take a patient-based and familycentred perspective, tailoring training to the diverse and emerging health care needs of the paediatric population ( Jones et al 2009;Leslie 2009).…”
Section: Training Needssupporting
confidence: 66%
“…This observation is in keeping with the Residency Review and Redesign project (R 3 P) participants conclusions in the US that residency training should be tailored to meet the diverse career needs of individuals who choose to care for disparate patients, in diverse settings, with a variety of health-related needs ( Jones et al 2009;Leslie 2009). Residency training programmes should allow flexibility and take a patient-based and familycentred perspective, tailoring training to the diverse and emerging health care needs of the paediatric population ( Jones et al 2009;Leslie 2009). Forrest et al's (1999) survey of the referral practices of general paediatricians to specialists suggested that educators should ensure that the 50 most commonly referred conditions (which were similar to the competencies surveyed in this study) are emphasized during paediatric residency training.…”
Section: Training Needssupporting
confidence: 66%
“…Instead of recommending general changes in the number of months in a particular setting or the required numbers of continuity clinics for all residency training programs, those participating in the R 3 P Project embraced encouraging diverse innovative approaches to improving education. 3,60 In this endeavor, we can profit from the experiences of internal medicine and family medicine, because both fields are going through a similar methodology to achieve improvements in their residency training programs. [61][62][63][64][65] It is our hope that creative approaches fostered under this process will enhance learning, improve patient and family outcomes, and lead to more efficient, effective pediatric care.…”
mentioning
confidence: 99%
“…1 To that end, the ABP began funding the Initiative for Innovation in Pediatric Education (IIPE) program in 2009 with the purpose of stimulating and facilitating innovation in pediatric education. 2 As a program, the IIPE comprised a director and a project support team who answered to the IIPE oversight committee.…”
Section: Carol Carraccio MD Ma Bmentioning
confidence: 99%